Landscapes of Social Transformation in the Salinas Province and the Eastern Pueblo World - Spielmann, Katherine A. (Book collections on Project MUSE., 2017)
Drawing on 16 seasons of field work, this volume provides an in-depth look at New Mexico's Salinas Pueblo and explains its relevance to Southwestern archaeology--Provided by publisher.